Immunohistochemical analysis of H3K27me3 demonstrates global reduction in group-A childhood posterior fossa ependymoma and is a powerful predictor of outcome - Panwalkar, Pooja; Pfister, Stefan; Korshunov, Andrey (Acta neuropathologica, 2017)
Posterior fossa ependymomas (EPN_PF) in children comprise two morphologically identical, but biologically distinct tumor entities. Group-A (EPN_PFA) tumors have a poor prognosis and require intensive therapy. In contrast, group-B tumors (EPN_PFB) exhibit excellent prognosis and the current consensus opinion recommends future clinical trials to test the possibility of treatment de-escalation in these patients. Therefore, distinguishing these two tumor subtypes is critical. EPN_PFA and EPN_PFB can be distinguished based on DNA methylation signatures, but these assays are not routinely available. We have previously shown that a subset of poorly prognostic childhood EPN_PF exhibits global reduction in H3K27me3. Therefore, we set out to determine whether a simple immunohistochemical assay for H3K27me3 could be used to segregate EPN_PFA from EPN_PFB tumors. We assembled a cohort of 230 childhood ependymomas and H3K27me3 immunohistochemistry was assessed as positive or negative in a blinded manner. H3K27me3 staining results were compared with DNA methylation-based subgroup information available in 112 samples [EPN_PFA (n = 72) and EPN_PFB tumors (n = 40)]. H3K27me3 staining was globally reduced in EPN_PFA tumors and immunohistochemistry showed 99% sensitivity and 100% specificity in segregating EPN_PFA from EPN_PFB tumors. Moreover, H3K27me3 immunostaining was sufficient to delineate patients with worse prognosis in two independent, non-overlapping cohorts (n = 133 and n = 97). In conclusion, immunohistochemical evaluation of H3K27me3 global reduction is an economic, easily available and readily adaptable method for defining high-risk EPN_PFA from low-risk posterior fossa EPN_PFB tumors to inform prognosis and to enable the design of future clinical trials.
Gesehen am 06.06.2017